Job Satisfaction amongst Academic Staff: A literature Review - Mehrad, Aida (Journal of Educational, Health and Community Psychology, 2015)
AbstractJob satisfaction assumed as a one of the main factor amongst academic staff and placed as a basic inner feeling for them. Moreover, the purpose of present literature review was to brilliant the role of job satisfaction at university; also, illustrated this inner organizational feeling as a principle positive motivator amongst academic staff. Lack of consideration to the presence of job satisfaction creates numerous difficulties at university, low level of job satisfaction likewise emerges some insufficient behaviors and reactions among academic staff. In other word, the existence of job satisfaction as basic human needs can develop and support performance of academic staff and conduct their organizational behavior in the accurate way. In general, the current literature review focused on the key role of job satisfaction at university and mentioned its effectiveness on performance, behavior, and reactions of academic staff at educational system.Key Words:Job Satisfaction, Academic Staff, University, Educational System